Toward Sustainable Water Governance? Taking Stock of Paradigms, Practices, and Sustainability Outcomes - Bilalova, Shahana; Newig, Jens; Villamayor-Tomas, Sergio (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
Governance is key to ensuring the sustainability of water systems in the long run. With the recognition of the complexities inherent in governing water resources, new and diverse governance models have started to emerge and be diffused to various contexts. This systematic review explores 223 cases from 165 studies on water governance and sustainability. We assess the cases based on water governance paradigms and how these paradigms relate to governance characteristics, water-related problématiques, and sustainability outcomes. Our results indicate a lack of knowledge cumulation and patterns connecting problématiques (e.g., “groundwater exploitation in agriculture”) and paradigms (e.g., “community-based management”). We found that the “integrated approach to water management” was the most common paradigm, and paradigms might manifest with various governance characteristics, some of which may not fully align with the paradigm's fundamental principles. While certain paradigms, such as “integrated approach to water management,” “participatory and collaborative governance,” and “community-based management,” are mostly associated with better sustainability outcomes, these successes should be interpreted cautiously due to the context-sensitive nature of paradigms and potential biases in the reviewed studies. These findings provide a basis for further diagnostic work and suggest the need for more nuanced approaches to water governance and sustainability.
Keywords: Effectiveness; Review; Sustainability Outcome; Water Governance Paradigm; Water Governance Trait